Burkholderia pseudomallei-specific recombinant protein and its potential in the diagnosis of melioidosis - Wongprompitak, P; Thepthai, C; Songsivilai, S; Dharakul, T (Asian Pacific journal of allergy and immunology, 2001)
Melioidosis is an important public health problem in Southeast Asia and Northern Australia. This disease is caused by the gram-negative bacilli, Burkholderia pseudomallei. Wide spectra of clinical manifestations are observed in melioidosis ranging from asymptomatic to septicemic infection. Although serodiagnostic methods of melioidosis have been improved significantly in recent years, a highly specific diagnostic test that can differentiate asymptomatic seropositive individuals and melioidosis patients remains to be the subject of current investigations. In this study, a B. pseudomallei-specific gene, pBps-1, expressing a novel 18.7 kDa recombinant protein was selected from genomic libraries of two B. pseudomallei virulent isolates by using pooled sera from septicemic melioidosis patients. Nucleotide sequence analysis demonstrated that this gene is unique and does not show substantial similarity with any known genes in the Genbank database. The Bps-1 recombinant protein was evaluated for its potential in serodiagnosis of melioidosis by Western blot analysis. A high degree of specificity was demonstrated using sera from healthy individuals in the endemic (98.5%) and non-endemic areas (100%), with moderate sensitivity (69.7%) in melioidosis patients. The study demonstrated that this approach can be used to obtain highly specific recombinant antigens such as that described in the present report. A combination of such antigens should provide materials for successful serodiagnosis of melioidosis in the endemic areas.